Alternatives to eye bank native tissue for corneal stromal replacement. (July 2017) - Brunette, Isabelle; Roberts, Cynthia J.; Vidal, François; Harissi-Dagher, Mona; Lachaine, Jean; Sheardown, Heather; Durr, Georges M.; Proulx, Stéphanie; Griffith, May
Abstract: Corneal blindness is a major cause of blindness in the world and corneal transplantation is the only widely accepted treatment to restore sight in these eyes. However, it is becoming increasingly difficult for eye banks to meet the increasing demand for transplantable tissue, which is in part due to population aging. Donor tissue shortage is therefore a growing concern globally and there is a need for alternatives to human donor corneas. Biosynthetic corneal substitutes offer several significant advantages over native corneas: Large-scale production offers a powerful potential solution to the severe shortage of human donor corneas worldwide; Good manufacturing practices ensure sterility and quality control; Acellular corneal substitutes circumvent immune rejection induced by allogeneic cells; Optical and biomechanical properties of the implants can be adapted to the clinical need; and finally these corneal substitutes could benefit from new advances in biomaterials science, such as surface coating, functionalization and nanoparticles. This review highlights critical contributions from laboratories working on corneal stromal substitutes. It focuses on synthetic inert prostheses (keratoprostheses), acellular scaffolds with and without enhancement of endogenous regeneration, and cell-based replacements. Accent is put on the physical properties and biocompatibility of these biomaterials, on the functional and clinical outcome once transplanted in vivo in animal or human eyes, as well as on the main challenges of corneal stromal replacement. Regulatory and economic aspects are also discussed. All of these perspectives combined highlight the founding principles of the clinical application of corneal stromal replacement, a concept that has now become reality. Highlights: Donor corneal tissue shortage is a growing concern globally. Optimization of traditional corneal transplantation results has reached a plateau. Biomaterials and bioengineering offer suitable alternatives to donor corneas. Various biomaterial properties must be assessed to ensure safe clinical transfer. Promising new technologies reveal an entirely new paradigm for corneal rehabilitation.